2018
DOI: 10.1002/cne.24523
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐responsive autonomic neurons in rat medulla oblongata

Abstract: Low blood glucose activates brainstem adrenergic and cholinergic neurons, driving adrenaline secretion from the adrenal medulla and glucagon release from the pancreas. Despite their roles in maintaining glucose homeostasis, the distributions of insulin-responsive adrenergic and cholinergic neurons in the medulla are unknown. We fasted rats overnight and gave them insulin (10 U/kg i.p.) or saline after 2 weeks of handling. Blood samples were collected before injection and before perfusion at 90 min. We immunope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 93 publications
(153 reference statements)
0
11
0
Order By: Relevance
“…Hypoglycemia initiates the activation of hypothalamic and medullary pathways that enhance pancreatic glucagon and adrenal medullary epinephrine secretion (24, 25, 5860). Recently, Senthilkumaran et al (49) used a diaminobenzidine staining method to demonstrate the presence of glucose-responsive neurons in the C1 and C3 medullary regions as well as in the chromaffin cells of the adrenal medulla. Similar diaminobenzidine staining methodology revealed that Fos expression is also present in the C1 and C3 regions after systemic 2-deoxyglucose (2-DG)-induced glucoprivation (41, 45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoglycemia initiates the activation of hypothalamic and medullary pathways that enhance pancreatic glucagon and adrenal medullary epinephrine secretion (24, 25, 5860). Recently, Senthilkumaran et al (49) used a diaminobenzidine staining method to demonstrate the presence of glucose-responsive neurons in the C1 and C3 medullary regions as well as in the chromaffin cells of the adrenal medulla. Similar diaminobenzidine staining methodology revealed that Fos expression is also present in the C1 and C3 regions after systemic 2-deoxyglucose (2-DG)-induced glucoprivation (41, 45).…”
Section: Discussionmentioning
confidence: 99%
“…This does not discount the possibility that caudal C1 neurons projecting to the medial hypothalamus (paraventricular and arcuate nucleus) are also contributing to the downstream epinephrine response; however, the activation of caudal C1 cells is more closely linked to behavioral responses such as feeding following insulin-induced hypoglycemia (10, 44, 54, 61). Furthermore, Senthilkumaran et al (49) showed that both caudal and rostral C1 cells are activated after insulin-induced hypoglycemia, so it would not be surprising if repeated hypoglycemia also reduced the activation of caudal C1 neurons, since the behavioral response to hypoglycemia (i.e., feeding) is reduced in HAAF (47). The present study falls short in providing an answer for what the relative contribution of caudal C1 neuronal activation is in terms of hypoglycemia-induced epinephrine secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there have been intensive efforts to understand how the central nervous system (Carus, 1814) [ 16 ] (CNS) (see Section 2.1 for the formal (italicized) atlas nomenclature used in this study) senses circulating levels of glucose and initiates counterregulatory responses, and how CNS impairments contribute to defective glucose counterregulation [ 17 , 18 , 19 , 20 ]. A compelling body of evidence has established a critical role for various rhombic brain (His, 1893) [ 21 ] (RB) regions in glucosensing, feeding and/or counterregulatory responses to glycemic challenges [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], with much of this work focused on the role of catecholaminergic neurons in the medulla (Winslow, 1733) [ 42 ] (MY) in these functions [ 17 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Certain neuronal populations in the hypothalamus (Kuhlenbeck, 1927) [ 52 ] (HY) also appear to be glucosensing and/or critical for counterregulation [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , …”
Section: Introductionmentioning
confidence: 99%
“…First, in terms of temporal dynamics, it is not fully understood how quickly RB neuronal networks track changes in glycemic status in vivo . Immunodetection of the transcription factor, Fos, has been used to track RB neuronal activation associated with glycemic challenge [30, 39, 42, 53, 75], but its protein expression typically peaks within 1–3 hours [77]. Thus, it is difficult to attribute its delayed expression to changes in glycemic status per se rather than to secondary effects set in motion by such changes.…”
Section: Introductionmentioning
confidence: 99%